Kinetic analysis of forwards, step-by-step and backwards stair descent - Cluff, Tyler (University of Ottawa (Canada), 2008)
The purpose of this research was to evaluate biomechanical differences in alternate stair descent strategies to determine the mechanisms by which these strategies modulate task mechanics Seventeen healthy subjects (9 males, 8 females) performed ten trials in four experimental conditions; forwards (FD), backwards (BD), step-by-step lead (SBSL) and trail (SBST) limbs. Results showed that peak ankle plantiflexor powers and work in BD and SBSL were similar in magnitude (p>0.05) and reduced relative to FD at initial contact (p<0.001) Similarly, the midstance peak plantiflexor moments, powers and work in FD and SBST were greater than both BD and SBSL (p<0.001). The plantiflexor moment and work in BD were larger than those at the SBSL limb (p<0.01), whereas power magnitudes were not significantly different (p>0.05). Lastly, peak moments, powers and work at push-off were greater in FD compared to all other conditions (p<0.001) and further, were larger in SBST relative to BD and SBSL (p<0.001). Peak moments, powers and work were similar in BD and SBSL conditions (p>0.05). Peak knee moments, powers and work were reduced during the eccentric midstance burst. Knee moments, powers and work were similar in FD and SBST (p>0.05), but were greater than BD and SBSL (p<0.001). Peak moments, powers and work were greater in BD compared to the SBSL limb (p<0.001). Thus, the step-by-step descent strategy is more appropriate for individuals with unilateral knee problems, whereas backwards descent is more suitable for bilateral quadriceps weakness. Peak hip powers and work were larger in BD relative to FD (p <0.001) during initial contact. Similarly, the extensor moment in BD was significantly larger than the flexor moment demonstrated in FD. No consistent stair or condition effects were observed for the concentric hip flexor burst at push-off in FD, SBSL and SBST conditions. Finally, this study considered foot clearance in stair descent. Clearance was greater in BD relative to FD, SBSL and SBST in the mid staircase region, but was similar at step 1, which represented the transition from standing to stair descent. No foot contacts, trips or stumbles were recorded, demonstrating the likelihood of contacting a stair edge in all patterns was nonexistent for these healthy participants. The present results have implications to improve functionality in stair descent for individuals that find the task difficult or painful. Future studies will likely consider the strategies employed during the initiation of stair descent by elderly and clinical populations to gain insight on the strategies used to minimize mechanical burden on both the joints and overlying musculature. Lastly, research should consider the effects of handrail use on alternate stair descent strategy mechanics, such as backwards and step-by-step descent.
Keywords: Health Sciences, Recreation.